2007
DOI: 10.1002/ejic.200700860
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Induced Luminescence Changes of Chromophore‐Quencher Tricarbonylpolypyridylrhenium(I) Complexes with 4‐Pyridinealdazine

Abstract: The new chromophore-quencher tricarbonylrhenium(I) complexes [Re(4,4Ј-X 2 -bpy)(CO) 3 -salts and characterized by spectroscopic, electrochemical, and photophysical techniques. In contrast to previously reported species with X = Me or H, these complexes emit at room temperature in CH 3 CN. The recovery of luminescence can thus be ascribed to the change of energy levels induced by adding electron-withdrawing substituents to the 2,2Ј-bipyridine ring, since the emissive Re II (X 2 bpy -) excited state becomes muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
(106 reference statements)
5
21
0
Order By: Relevance
“…Functionalised polypyridine (NN) receptors in [Re(CO) 3 (NN)(L)] + (L = pyridine-based ligand) complexes have been employed as: turn-on emission sensors for metal ions, 73 anion recognition 74 and indole-binding proteins; 75 a turn-off emission sensor for biologically relevant oxometalates; 76 an off-on-off emission sensor for pH changes. 77 Photoinduced geometry changes associated with the MLCT excited state of [Re-(L 10 )(CO) 3 Cl], probed in a combined DFT/Raman spectroscopy study, are consistent with simple MO theory descriptions of the charge-transfer process. 78 Photocyclisation of the diarylethylene ligand in [Re(L 11 )(CO) 3 Cl] occurs in the 3 MLCT state upon prolonged excitation (l = 352 nm) which results in a large red-shift of the absorption maximum, an example of metal coordination-assisted near-IR photochromic behaviour.…”
Section: Rhenium Complexessupporting
confidence: 64%
“…Functionalised polypyridine (NN) receptors in [Re(CO) 3 (NN)(L)] + (L = pyridine-based ligand) complexes have been employed as: turn-on emission sensors for metal ions, 73 anion recognition 74 and indole-binding proteins; 75 a turn-off emission sensor for biologically relevant oxometalates; 76 an off-on-off emission sensor for pH changes. 77 Photoinduced geometry changes associated with the MLCT excited state of [Re-(L 10 )(CO) 3 Cl], probed in a combined DFT/Raman spectroscopy study, are consistent with simple MO theory descriptions of the charge-transfer process. 78 Photocyclisation of the diarylethylene ligand in [Re(L 11 )(CO) 3 Cl] occurs in the 3 MLCT state upon prolonged excitation (l = 352 nm) which results in a large red-shift of the absorption maximum, an example of metal coordination-assisted near-IR photochromic behaviour.…”
Section: Rhenium Complexessupporting
confidence: 64%
“…The fact that k q < k dif /9 could be attributed to an important enhanced intersystem crossing between singlet and triplet charge-transfer intermediate states or even of the enhancement of reaction 6. It has been suggested that the presence of the heavy ion Ru (II) would enhance spin-forbidden pathways, 10 contributing to a k q value lower than the statistically expected one. Another fact of this mechanism is that the observed quenching rate constant k q = 1 k q + 3 k q , where 1 k q and 3 k q are the quenching rate constant through the singlet and triplet channels, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…UV/Vis spectroelectrochemical experiments were performed in CH 3 CN (0.1 M TBAH) using a 1 mm path‐length spectroelectrochemical cell from CH Instruments, with Pt grid as working electrode, Pt wire as counter electrode, and Ag/AgCl (3 M KCl) as reference electrode. Lifetimes and transient spectra of the lowest‐lying 3 MLCT excited states were obtained with a laser flash photolysis setup as described previously 1b. Lifetimes were also determined by a time‐correlated single‐photon counting (TCSPC) technique, with a Tempro‐01 apparatus from Horiba Jobin Yvon (Glasgow, U.K.), using as the excitation pulse source an ultrafast (460±27) and (340±15) nm Nanoled from Horiba operating at 250 kHz.…”
Section: Methodsmentioning
confidence: 99%